ANÁLISE ERGONÔMICA EM UMA OFICINA MECÂNICA: UM ESTUDO DE CASO EM EMPREENDIMENTOS DE PEQUENO PORTE (REMUNOM, 2024)
The automotive mechanic is a professional exposed to various risks at work. Among them are ergonomic risks. The objective of this article was to analyze the ergonomics of a small mechanical workshop.  The methodology used was a case study, descriptive, experimental, quantitative in nature, which consisted of analyzing lighting, odor and noise in the work environment; application of the AET questionnaire (ergonomic work analysis) and application of the Nordic musculoskeletal questionnaire (NMQ).  The sample was the analysis of one (1) mechanical workshop, in which three (3) mechanics work. As a result, in relation to the work environment, the maximum noise reached 70 dB, in relation to odor, the amount of carbon dioxide in the work environment was 189.5 CO2, being below tolerable, not causing harm to health, as the lighting in the work environment was below the recommended 129 lux, which could cause eye strain. Regarding the NMQ, workers reported pain in the upper part of the spine, but no type of absence or illness was reported in recent months. In this way, we observed that the Ergonomic Work Analysis carried out in a mechanical workshop specializing in vehicles, showed that the workshop workers consider the work tiring, a little heavy, complaining only of pain in the upper part of the spine, and not presenting any type of medical leave. In relation to AET, we can observe a deficit in the lighting of the space in the workshop. We conclude that it is important to analyze the work environment, as a comfortable environment brings numerous advantages to the worker, such as better quality of work and a lower rate of absences. Keywords: Ergonomics; Mechanical workshop; Worker's health.